OSPORT - A Practical Tool for Porting or Adjusting Operating System Source-Code - Souza, Osvaldo de; Castro, Helano S. (Anais do Workshop de Sistemas Operacionais (WSO); 2007: Anais do IV Workshop de Sistemas Operacionais, 2007)
Many projects frequently uses the “trial and error” approach for Operating System (OS) porting or maintenance, resulting in incomplete or inconsistent modifications. This can be partially explained due the absence of useful tools helping the source-code analysis, in order to determine what source-code must be modified for adjusting it to another hardware platform. In this paper, we present an application called OSPORT, based on a seminal method for detecting OS parts that should be adjusted in order to port or adjust the OS for a new hardware platform. The OSPORT provides: a complete list of source-codes that must be adjusted; the interdependence between these source-codes; the priority order of modifications for each source-code; and an effort-based schedule, in order to plan the modifications.